Joint analysis of the discount factor and payoff parameters in dynamic discrete choice models - Tatiana Komarova; Fabio Sanches; Daniel Silva Junior; Sorawoot Srisuma (Quantitative Economics, 2018)
Most empirical and theoretical econometric studies of dynamic discrete choice models assume the discount factor to be known. We show the knowledge of the discount factor is not necessary to identify parts, or even all, of the payoff function. We show the discount factor can be generically identified jointly with the payoff parameters. On the other hand, it is known the payoff function cannot be nonparametrically identified without any a priori restrictions. Our identification of the discount factor is robust to any normalization choice on the payoff parameters. In IO applications, normalizations are usually made on switching costs, such as entry costs and scrap values. We also show that switching costs can be nonparametrically identified, in closed-form, independently of the discount factor and other parts of the payoff function. Our identification strategies are constructive. They lead to easy to compute estimands that are global solutions. We illustrate with a Monte Carlo study and the dataset used in Ryan ().
Keywords: C14; C25; C51; 330; Discount factor; dynamic discrete choice problem; identification; estimation; switching costs